Research on Security Authentication Mechanism for IoT Devices: A Digital Identity Authentication-Based Solution - Cui, Jingbo (International Journal of Computer Science and Information Technology, 2025)
This paper proposes a lightweight authentication scheme for IoT devices based on an improved ECC algorithm. By optimizing the key agreement process and introducing a temporary session key generation mechanism, the scheme significantly reduces authentication overhead and resource consumption for terminal devices. A weighted trust evaluation model based on device behavior characteristics is designed to enhance anomaly detection capabilities. A distributed key management architecture is adopted to address key management challenges in large-scale device authentication scenarios. The proposed scheme has been validated in the large-scale deployment of smart meter terminals, demonstrating its ability to ensure security while maintaining lightweight characteristics and scalability.